Utilization of food waste and by-products in the fabrication of active and intelligent packaging for seafood and meat products - Zainal Arifin, Maryam; Mohd Adzahan, Noranizan; Zainal Abedin, Nur; Lasik-Kurdyś, Małgorzata (MDPI, 2023)
Research on the utilization of food waste and by-products, such as peels, pomace, and seeds has increased in recent years. The high number of valuable compounds, such as starch, protein, and bioactive materials in waste and by-products from food manufacturing industries creates opportunities for the food packaging industry. These opportunities include the development of biodegradable plastics, functional compounds, active and intelligent packaging materials. However, the practicality, adaptability and relevance of up-scaling this lab-based research into an industrial scale are yet to be thoroughly examined. Therefore, in this review, recent research on the development of active and intelligent packaging materials, their applications on seafood and meat products, consumer acceptance, and recommendations to improve commercialization of these products were critically overviewed. This work addresses the challenges and potential in commercializing food waste and by-products for the food packaging industry. This information could be used as a guide for research on reducing food loss and waste while satisfying industrial demands.